The Ath5 proneural genes function upstream of Brn3 POU domain transcription factor genes to promote retinal ganglion cell development - Liu, Wei (The National Academy of Sciences, 2001)
During retinogenesis, the Xenopus basic helix–loop–helix transcription factor Xath5 has been shown to promote a ganglion cell fate. In the developing mouse and chicken retinas, gene targeting and overexpression studies have demonstrated critical roles for the Brn3 POU domain transcription factor genes in the promotion of ganglion cell differentiation. However, the genetic relationship between Ath5 and Brn3 genes is unknown. To understand the genetic regulatory network(s) that controls retinal ganglion cell development, we analyzed the relationship between Ath5 and Brn3 genes by using a gain-of-function approach in the chicken embryo. We found that during retinogenesis, the chicken Ath5 gene (Cath5) is expressed in retinal progenitors and in differentiating ganglion cells but is absent in terminally differentiated ganglion cells. Forced expression of both Cath5 and the mouse Ath5 gene (Math5) in retinal progenitors activates the expression of cBrn3c following central-to-peripheral and temporal-to-nasal gradients. As a result, similar to the Xath5 protein, both Cath5 and Math5 proteins have the ability to promote the development of ganglion cells. Moreover, we found that forced expression of all three Brn3 genes also can stimulate the expression of cBrn3c. We further found that Ath5 and Brn3 proteins are capable of transactivating a Brn3b promoter. Thus, these data suggest that the expression of cBrn3c in the chicken and Brn3b in the mouse is initially activated by Ath5 factors in newly generated ganglion cells and later maintained by a feedback loop of Brn3 factors in the differentiated ganglion cells.